GMAT Question of the Day - Daily to your Mailbox; hard ones only

 It is currently 16 Nov 2018, 18:38

### GMAT Club Daily Prep

#### Thank you for using the timer - this advanced tool can estimate your performance and suggest more practice questions. We have subscribed you to Daily Prep Questions via email.

Customized
for You

we will pick new questions that match your level based on your Timer History

Track

every week, we’ll send you an estimated GMAT score based on your performance

Practice
Pays

we will pick new questions that match your level based on your Timer History

## Events & Promotions

###### Events & Promotions in November
PrevNext
SuMoTuWeThFrSa
28293031123
45678910
11121314151617
18192021222324
2526272829301
Open Detailed Calendar
• ### Free GMAT Strategy Webinar

November 17, 2018

November 17, 2018

07:00 AM PST

09:00 AM PST

Nov. 17, 7 AM PST. Aiming to score 760+? Attend this FREE session to learn how to Define your GMAT Strategy, Create your Study Plan and Master the Core Skills to excel on the GMAT.
• ### GMATbuster's Weekly GMAT Quant Quiz # 9

November 17, 2018

November 17, 2018

09:00 AM PST

11:00 AM PST

Join the Quiz Saturday November 17th, 9 AM PST. The Quiz will last approximately 2 hours. Make sure you are on time or you will be at a disadvantage.

# If (6 + 2/x)(x - 4) = 0, and x does not equal 4, then x =

Author Message
TAGS:

### Hide Tags

Math Expert
Joined: 02 Sep 2009
Posts: 50619
If (6 + 2/x)(x - 4) = 0, and x does not equal 4, then x =  [#permalink]

### Show Tags

19 Oct 2017, 23:13
00:00

Difficulty:

5% (low)

Question Stats:

93% (01:07) correct 7% (02:09) wrong based on 91 sessions

### HideShow timer Statistics

If $$(6 + \frac{2}{x})(x - 4) = 0$$, and x does not equal 4, then x =

(A) -6
(B) -4
(C) -1/3
(D) 1/3
(E) 3

_________________
Senior PS Moderator
Joined: 26 Feb 2016
Posts: 3307
Location: India
GPA: 3.12
If (6 + 2/x)(x - 4) = 0, and x does not equal 4, then x =  [#permalink]

### Show Tags

20 Oct 2017, 00:03
Bunuel wrote:
If $$(6 + \frac{2}{x})(x - 4) = 0$$, and x does not equal 4, then x =

(A) -6
(B) -4
(C) -1/3
(D) 1/3
(E) 3

$$(6 + \frac{2}{x})(x - 4) = 0$$

$$6x - \frac{8}{x} - 24 + 2 = 0$$

$$6x - \frac{8}{x} - 22 = 0$$

$$6x^2 - 22x - 8 = 0$$

$$6x^2 - 24x + 2x - 8 = 0$$ => $$6x(x - 4) + 2(x - 4) = 0$$ => $$(6x+2)(x-4) = 0 => x=4$$ or $$-\frac{1}{3}$$

Since x cannot be 4, the other value of x = $$-\frac{1}{3}$$(Option C)
_________________

You've got what it takes, but it will take everything you've got

Status: Preparing for GMAT
Joined: 25 Nov 2015
Posts: 983
Location: India
GPA: 3.64
Re: If (6 + 2/x)(x - 4) = 0, and x does not equal 4, then x =  [#permalink]

### Show Tags

20 Oct 2017, 03:37
(6+$$\frac{2}{x}$$)(x-4)=0
$$\frac{(6x+2)}{x}$$ * (x-4)=0
(6x+2) * (x-4)=0 ---Cross multiplying by x
Therefore, x = $$\frac{-2}{6}$$ = $$\frac{-1}{3}$$ or 4
Since x is not equal to 4, x = $$\frac{-1}{3}$$
_________________

Please give kudos, if you like my post

When the going gets tough, the tough gets going...

Senior SC Moderator
Joined: 22 May 2016
Posts: 2099
If (6 + 2/x)(x - 4) = 0, and x does not equal 4, then x =  [#permalink]

### Show Tags

20 Oct 2017, 06:37
Bunuel wrote:
If $$(6 + \frac{2}{x})(x - 4) = 0$$, and x does not equal 4, then x =

(A) -6
(B) -4
(C) -1/3
(D) 1/3
(E) 3

You do not have to do much math here. Set the first term equal to 0 and you have your answer.

By the zero product rule, if
a * b = 0, then a = 0, or b = 0, or both = 0

x does not equal 4. Hence
(x - 4) cannot = 0. Therefore:

The first term, $$(6 + \frac{2}{x})$$ must equal 0.

(Plain English: you cannot have a product of 0 unless one or both of the factors is 0.)

$$(6 + \frac{2}{x}) = 0$$

$$6 = - \frac{2}{x}$$

$$6x = - 2$$

$$x = -\frac{2}{6} = -\frac{1}{3}$$

Intern
Joined: 30 May 2017
Posts: 9
Re: If (6 + 2/x)(x - 4) = 0, and x does not equal 4, then x =  [#permalink]

### Show Tags

20 Oct 2017, 08:34
If x cannot be 4, (6+2/x) must be equal 0 to multiply (x-4) and obtain zero.

6+ 2/x = 0
2/x = -6
x = - 1 / 3
Target Test Prep Representative
Status: Founder & CEO
Affiliations: Target Test Prep
Joined: 14 Oct 2015
Posts: 4170
Location: United States (CA)
Re: If (6 + 2/x)(x - 4) = 0, and x does not equal 4, then x =  [#permalink]

### Show Tags

24 Oct 2017, 05:16
Bunuel wrote:
If $$(6 + \frac{2}{x})(x - 4) = 0$$, and x does not equal 4, then x =

(A) -6
(B) -4
(C) -1/3
(D) 1/3
(E) 3

Since x ≠ 4, we see that x - 4 can’t be 0, and therefore, in order for the product to equal 0, 6 + 2/x must equal 0:

6 + 2/x = 0

2/x = -6

2 = -6x

-1/3 = x

_________________

Scott Woodbury-Stewart
Founder and CEO

GMAT Quant Self-Study Course
500+ lessons 3000+ practice problems 800+ HD solutions

Manager
Joined: 09 Aug 2017
Posts: 62
Location: United States
Concentration: Technology
GMAT 1: 640 Q44 V33
GMAT 2: 630 Q47 V29
WE: Research (Investment Banking)
Re: If (6 + 2/x)(x - 4) = 0, and x does not equal 4, then x =  [#permalink]

### Show Tags

27 Oct 2017, 08:13
1
I got C, but I was an idiot of massive proportions and totally missed the shortcut. The hint is that (x-4) will not give you zero. Hence, you only need to solve for (6+[2][/x])=0.

I am guessing this cost me about 50 seconds and unneeded stress.
_________________

I'd love to hear any feedback or ways to improve my problem solving. I make a lot of silly mistakes. If you've had luck improving on stupid mistakes, I'd love to hear how you did it.

Also, I appreciate any kudos.

Re: If (6 + 2/x)(x - 4) = 0, and x does not equal 4, then x = &nbs [#permalink] 27 Oct 2017, 08:13
Display posts from previous: Sort by